THE EFFECTIVENESS OF PARTICIPATORY LEARNING AND ACTION METHOD IN INCREASING KNOWLEDGE IN STUNTING PREVENTION AMONG MOTHERS - Erik Kusuma; Ayu Dewi Nastiti; R.A Helda Puspitasari; Dwining Handayani (UPT Penerbitan Universitas Jember, 2023)
Background: Stunting is a condition where a baby or toddler experiences chronic malnutrition which has an impact on the child's low height. Participatory Learning Approach (PLA) is an alternative learning model that is used to increase the active participation of participants. This study aims to determine the effect of the Participatory Learning Approach (PLA) method in increasing mothers' knowledge in stunting prevention. Methods: The design of this study was quasi-experimental, with a pre and post test approach with a control group design. Respondents to this study were 50 mothers and prospective mothers who were divided into the intervention group (n=27) and the control group (n=23). The sampling technique used is convenience sampling. Respondents were invited to take part in a one-day learning program called Stunting Awareness Day (3S). In the 3S program, the intervention group was given health education using the PLA method, while the control group was given the traditional lecture method. This questionnaire is used to measure respondents' knowledge of stunting prevention before learning (pretest) and after learning (posttest). The data obtained were analyzed using paired t test and independent t test. Results: The results of this study showed that there was a significant difference between participatory learning methods and traditional approaches in increasing mothers' knowledge about stunting prevention (p = 0.002≤0.05), the increase in knowledge in the intervention group was more significant than the control group. Conclusions: The PLA and lecture learning methods can be used to increase respondents' knowledge in stunting prevention.